South Asian security, futures : a dialogue of directors regional strategic studies institutes - Banerjee, Dipankar; Banerjee, Dipankar; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (Colombo : Regional Centre for Strategic Studies, 2002)
Papers presented at two conferences.
Keywords: National security -- South Asia -- Congresses; Security, International -- Social aspects -- Congresses; South Asia -- Foreign relations -- Congresses; South Asia -- strategic aspects -- Congresses